Measuring content validity: tadabbur Al Quran and sejahtera living - Ismail, Nurussyifa’; Nordin, Mohamad Sahari; Ismail, Halim (Asian Scholars Network (ASNet), 2023)
Abstract: This research aims to examine the content validity of students’ Tadabbur Al Quran and Sejahtera Living using the Content Validity Ratio (CVR). The research was conducted through the evaluation of 8 expert panels with a purposive sampling technique. Expert panels were divided into two categories: professional and field experts. Five professional experts are lecturers at International Islamic University Malaysia and are involved with their respective expertise in the tadabbur Al Quran. Three field experts consisted of one doctor of philosophy (PhD) and two master’s candidates who are studying at the International Islamic University Malaysia and specializing in particular fields of study (Al Quran and Sunnah). The scale contains two aspects: tadabbur Al Quran and students’ Sejahtera living. Tadabbur Al Quran is conceptualized in three constructs with 17 items. Meanwhile, there are five constructs with 21 items for students' Sejahtera living. The results of the research show that the scale has good content validity and proved that the scale has great potential to be promoted as a good scale of the Tadabbur Al Quran and students’ Sejahtera Living. It is suggested to apply more sophisticated statistical analysis, such as